Eye-tracker illumination - KULDKEPP MATTIAS; BLIXT PETER; SKOGOE MAARTEN; HAINZL RICHARD (2018)
A subject (180) is illuminated whose movements of at least one eye are to be registered by an eye-tracker for producing resulting data (D EYE ). To this aim, a coherent light source in light producingmeans (140) produces at least one well-defined light beam (L1, L2). A diffractive optical element is arranged between the coherent light source and an output from the light producing means (140). Thediffractive optical element is configured to direct a light beam (L1) towards at least a first designated area (A1) estimated to cover the at least one eye of the subject (180). Image registering means (150) registers light from the at least one light beam (L1, L2) having been reflected against the subject (180). The resulting data (D EYE ) are produced in response to these light reflections, which resulting data (D EYE ) represent movements of the at least one eye of the subject (180). 种被照明的对象(180)，通过眼睛追踪器注册所述被照明对象的至少只眼睛的移动，用于生成结果数据(D)。为了实现上述目的，光生成装置(140)中的相干光源生成至少个良好定义的光束(L1，L2)。衍射光学元件被布置在干涉光源和光生成装置(140)的输出之间。衍射光学元件